PELATIHAN PEMBUATAN TEH HERBAL KULIT BUAH PALA DI DESA LILIBOOI, KECAMATAN LEIHITU BARAT, KABUPATEN MALUKU TENGAH - Palijama, Syane; Ega, L.; Breemer, R.; Polnaya, F. J. (MAANU: Jurnal Pengabdian Kepada Masyarakat, 2024)
Tea is a drink that has long been known and has experienced a lot of food diversification in producing various types of tea drinks whose raw materials do not come from Camelia sinensis tea leaves but come from flowers, seeds, leaves, roots, fruit peel, and fruit flesh from various This type of plant is also known as herbal tea. The herb has a distinctive aroma, taste, and bioactive components that benefit health. Herbal tea of nutmeg peel has advantages over non-herbal tea, namely that it is effective as a functional drink or can also be used as a refreshing drink for the body. In making tea, a drying process is carried out, which aims to reduce the water content to a specific limit in the raw materials and inhibit microbial growth so that herbal tea can be stored for a long time and is not easily damaged during storage. Several drying methods can be used to make herbal tea, one of which is roasting. The roasting process in making this tea will result in the product experiencing color, texture, and flavor changes. Through this activity, the community's knowledge, skills, and herbal tea products produced can be used as business opportunities